2017
DOI: 10.1109/tns.2017.2705522
|View full text |Cite
|
Sign up to set email alerts
|

Radiation hardness of dsipm sensors in a proton therapy radiation environment

Abstract: Abstract-In vivo verification of dose delivery in proton therapy by means of positron emission tomography (PET) or prompt gamma imaging is mostly based on fast scintillation detectors. The digital silicon photomultiplier (dSiPM) allows excellent scintillation detector timing properties and is thus being considered for such verification methods. We present here the results of the first investigation of radiation damage to dSiPM sensors in a proton therapy radiation environment. Radiation hardness experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…It has been estimated that a prompt gamma detector placed vertically at a distance of 30 cm from a 200-MeV proton beam is hit by 2 × 10 −5 neutrons/cm 2 /stopped proton [113]. In summary, assuming 380 patients/yr, the dose-verified detector should withstand at least fluences of 10 11 neutrons/cm 2 to operate without degradation for at least 5 yr [114]. Possible detector performance degradation due to these secondary neutrons, despite being a topic of relatively small interest, should not be overlooked when selecting scintillation crystals for proton therapy monitoring systems.…”
Section: Proton Therapymentioning
confidence: 99%
“…It has been estimated that a prompt gamma detector placed vertically at a distance of 30 cm from a 200-MeV proton beam is hit by 2 × 10 −5 neutrons/cm 2 /stopped proton [113]. In summary, assuming 380 patients/yr, the dose-verified detector should withstand at least fluences of 10 11 neutrons/cm 2 to operate without degradation for at least 5 yr [114]. Possible detector performance degradation due to these secondary neutrons, despite being a topic of relatively small interest, should not be overlooked when selecting scintillation crystals for proton therapy monitoring systems.…”
Section: Proton Therapymentioning
confidence: 99%
“…It is a low photon flux silicon sensor with an area ranging typically between 1 mm 2 and 9 mm 2 and an internal gain of reached at a bias ranging between 20 V and 60 V. Modern commercially available SiPMs exhibit photon detection efficiency up to 40% at 420 nm and single photon time resolution less than 100 ps (FWHM) [ 32 , 33 , 34 ]. Radiation hardness is currently under investigation [ 35 ]. Due to their compact size and simple required readout electronics, they are substituting the traditional photomultiplier tubes in PET instrumentation for proton therapy monitoring systems.…”
Section: Introductionmentioning
confidence: 99%
“…Dendooven and coll. [68] have made an experiment with bare digital SiPMs to test the radiation hardness of such devices in a geometry configuration typical of in-beam PET operation. They found that the dark count rate (DCR) became too large for successful operation after the equivalent of a few weeks in a proton therapy treatment room (about 5 × 10 13 protons.…”
Section: Hadrontherapymentioning
confidence: 99%